Developing Master Curves, Binder Viscosity and Predicting Dynamic Modulus of Polymer-Modified Asphalt Mixtures - Nega, Ainalem; Ghadimi, Behzad; Nikraz, Hamid (http://www.ijetch.org/, 2015)
The complex moduli relationship related mixture moduli to temperature and time rate of loading has been an integral part of several mechanistic-empirical (M-E) design procedures used throughout of the world. Seven asphalt concrete mixtures of different types of polymer modified binders (PMB) were produced in a laboratory to modify performance of asphalt mixture. The main role of this research is to evaluate the influence of these polymer modifiers on the pavement performance of asphalt mixture with the dynamic modulus, |E*| of hot-mix asphalt (HMA) mixture indicator in a laboratory test for Mainroad Western Australia and Fulton Hogan. In this study, the influence of temperature, loading frequency, and confining pressure on the dynamic characteristic of asphalt mixture were analysis, master curves of dynamic modulus of HMA mixtures were developed and data’s were interpreted. Results showed that AC10 5.7% A35P (EVA) M7 B5, AC10 5.7% C450 M10 B5 and AC10 Multi 600/700 M5 B4 mixes method were the more efficient and effective in all categories of asphalt performance measures for strength and durability of HMA as compared to others polymer modifiers. A very good correlation (R2 = 1) was found for each polymer modifier. This suggested that laboratory test using a various temperatures and loading frequencies can improve pavement mix design, lab and field control and assurance. A strong correlation between binder viscosity and temperature [R2 = 1] for polymer modified asphalt mixture.